2010
DOI: 10.3171/2010.2.jns091707
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in neurooncology—age matters

Abstract: These age differences clearly warn against consolidating the QOL or QOH scores of younger and older adults, and instead suggest that age at diagnosis is essential when considering patient perspective, and when establishing tailored support programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Ever since the publication of important functional studies such as the brain maps acquired by Ojemann et al in 117 epilepsy patients and showing a great variability in the speech localization, a greater emphasis has been placed on the study of the function, thereby realizing that reliance on topographical anatomy alone is inadequate 54 . Moreover, studies in neuro-oncology are now included as an integral facet of the evaluation of patients quality of life data as well as neuro-cognitive evaluations, leaning toward a more inclusive and integrated view of the patient as an individualwhole [55][56][57] . The concept of brain functioning now involves a dynamic organization of networks connecting several cortical and subcortical areas of the brain 1,58 .…”
Section: Discussionmentioning
confidence: 99%
“…Ever since the publication of important functional studies such as the brain maps acquired by Ojemann et al in 117 epilepsy patients and showing a great variability in the speech localization, a greater emphasis has been placed on the study of the function, thereby realizing that reliance on topographical anatomy alone is inadequate 54 . Moreover, studies in neuro-oncology are now included as an integral facet of the evaluation of patients quality of life data as well as neuro-cognitive evaluations, leaning toward a more inclusive and integrated view of the patient as an individualwhole [55][56][57] . The concept of brain functioning now involves a dynamic organization of networks connecting several cortical and subcortical areas of the brain 1,58 .…”
Section: Discussionmentioning
confidence: 99%
“…The announcement of such a diagnosis and poor prognosis, the effects of the tumor on cognition and functionality, and the toxicity of treatments have rapid and important consequences on the everyday life of patients and their relatives [2,3]. These social, emotional, psychological and physical consequences have already been described [4][5][6], indicating an important quality of life (QoL) alteration at a level that is not normally observed in other cancers [7][8][9][10][11][12][13]. Due to these major lifestyle disruptions, there is an interest in studying how patients and caregivers handle the problems of daily life and how the Abstract Patients with high-grade gliomas (HGG) and their caregivers have to confront a very aggressive disease that produces major lifestyle disruptions.…”
Section: Introductionmentioning
confidence: 95%
“…Large tumors were also associated with poorer self-assessed social support, which would be consistent with evidence that more severe clinical conditions are more difficult to care for than less severe conditions, and thus lead to the experience of less satisfying social care 19 . Interestingly, a close relationship between tumor volume and social dimensions of quality of life was also observed by Salo et al 16 . In their study, the authors found that, among a group of brain tumor patients presenting with varied tumor grades, larger tumors were associated with more pain and greater social isolation at baseline (i.e., preoperative visit).…”
Section: Discussionmentioning
confidence: 55%
“…Before running these correlations, however, we controlled for potential confounds by detrending all of our QOL scores from the effects of age and tumor location. Age and tumor location were chosen as control variables because they can influence QOL independently from the effects of tumor volume 16,17 . Detrending was carried out using linear regression such that age and tumor location were simultaneously entered as predictors of T1 QOL.…”
Section: Statistical Analysesmentioning
confidence: 99%